Mortality of insects and quality of maize grains in hermetic and non-hermetic storage - Priscila C. Viebrantz (Revista Brasileira de Engenharia Agrícola e Ambiental - Agriambi, 2016)
ABSTRACT Due to the need to improve the quality and safety of foods, chemical methods used to control grain pests have been replaced by alternative methods. For example, modified atmosphere within the storage units has been used. Therefore, the objective was to evaluate maize grain quality and mortality of insects of the species Sitophilus zeamais and Tribolium castaneum in hermetic and non-hermetic environments for 50 days of storage. The hermetic units consisted of polyethylene "bags" with capacity for 60 kg. A cage with 20 adults of each species and 200 g of maize was placed inside each unit. The oxygen level was quantified every five days. Evaluations of insect mortality and survival occurred at 10, 20, 30, 40 and 50 days of storage. At 0, 30 and 50 days, density, moisture and fungal incidence analyses were conducted. The airtight system is efficient in the control of insects, with satisfactory mortality values for both species. Insects favor the development of fungi during the storage, regardless of the storage system.